Co zrobić z bestią? Metafora jako narzędzie kategoryzacji niektórych ludzi na przykładzie ustawy z dnia 22 listopada 2013 r. o postępowaniu wobec osób z zaburzeniami psychicznymi stwarzających zagrożenie życia, zdrowia lub wolności seksualnej innych osób - Wojtczak, Sylwia (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The paper is to show the consequences of using in public and legal discourse some expressions, which disseminate certain metaphors in the individual and collective cognition. The analysed example is the expression ‘the act about the beasts’ used widely in Poland towards an act of 22 of November 2013 about a procedure towards persons with psychic disorders resulting a risk for life, health and sexual freedom of other persons. Such an identification of the act has been a realization of the metaphor PERSON WITH PSYCHIC DISORDERS RESULTING A RISK FOR LIFE, HEALTH AND SEXUAL FREEDOM OF OTHER PERSONS IS A BEAST. This metaphor may be a psychological means to facilitate dehumanized perception of certain human beings.